2015
DOI: 10.1016/j.jpainsymman.2014.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Gabapentin for Uremic Pruritus and Restless Legs Syndrome in Conservatively Managed Patients With Chronic Kidney Disease

Abstract: Gabapentin is a viable treatment for conservatively managed CKD and ESKD patients with pruritus and/or RLS, but side effects are common. Gabapentin should be used with caution although higher doses do not appear to be a factor associated with side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…51 In the comparison group of patients on dialysis, gabapentin was found to be similarly effective at a similar average dose; however, the rate of side effects in the dialysis group was significantly lower at only 14%, although the rate of drug discontinuation was not statistically different. 51 Gunal et al 52 enrolled 25 patients on HD in a randomized, placebo-controlled, double-blind trial of gabapentin at 300 mg three times per week for 4 weeks after dialysis and reported a significant response, namely a decrease in mean VAS score from 7.9 to 1.2, with no participants needing to drop out because of secondary side effects. Other small-scale studies have shown similar improvement in pruritus with doses of 100 or 300 mg of gabapentin after hemodialysis.…”
Section: Treatmentmentioning
confidence: 83%
See 3 more Smart Citations
“…51 In the comparison group of patients on dialysis, gabapentin was found to be similarly effective at a similar average dose; however, the rate of side effects in the dialysis group was significantly lower at only 14%, although the rate of drug discontinuation was not statistically different. 51 Gunal et al 52 enrolled 25 patients on HD in a randomized, placebo-controlled, double-blind trial of gabapentin at 300 mg three times per week for 4 weeks after dialysis and reported a significant response, namely a decrease in mean VAS score from 7.9 to 1.2, with no participants needing to drop out because of secondary side effects. Other small-scale studies have shown similar improvement in pruritus with doses of 100 or 300 mg of gabapentin after hemodialysis.…”
Section: Treatmentmentioning
confidence: 83%
“…Recently, Cheikh Hassan et al 51 published their results from a single-center retrospective cohort study testing the safety and efficacy of gabapentin for the treatment of restless legs syndrome and pruritus in patients with renal disease ranging from stage 3 CKD to ESRD. They specifically assessed gabapentin use in a group of 34 patients managed conservatively (ie, without dialysis) and compared the results with results from a group of 15 patients on dialysis.…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Cheikh Hassan et al studied the effect of gabapentin on relieving pruritus in dialysis patients (22). However, its use in dialysis patients requires accurate dose adjustments, and various studies have shown that neurotoxicity and coma occur in the absence of precise gabapentin dosing (23,24).…”
Section: Discussionmentioning
confidence: 99%